Revealing age-related changes of adult hippocampal neurogenesis - Ziebell, Frederik; Dehler, Sascha; Martín-Villalba, Ana; Marciniak-Czochra, Anna (bioRxiv beta, 2017)
In the adult hippocampus, neural stem cells (NSCs) continuously produce new neurons that integrate into the neuronal network to modulate learning and memory. The amount and quality of newly generated neurons decline with age, which can be counteracted by increasing intrinsic Wnt activity in NSCs. However, the precise cellular changes underlying this age-related decline or its rescue through Wnt remain unclear. The present study combines development of a mathematical model and experimental data to address features controlling stem cell dynamics. We show that available experimental data fit a model in which quiescent NSCs can either become activated to divide or undergo depletion events, consisting of astrocytic transformation and apoptosis. Additionally, we demonstrate that aged NSCs remain longer in quiescence and have a higher probability to become re-activated versus being depleted. Finally, our model explains that high NSC-Wnt activity leads to longer time in quiescence while augmenting the probability of activation.